Public Perception of Nurses’ Professional Image: A Post-Pandemic Analysis - Nietes, Halleberry; Panganiban, Shem; Paciente, Tisha Belle; Pacheco, Dvien Lehn; Oaing, Venisse Julianne; Pacle, Maxine Dorothy Amor; Penuela, Ayesha (Celebes Nursing Journal, 2025)
Introduction: Nursing, a cornerstone of healthcare, is often overshadowed by stereotypes and misconceptions that influence public perception. Objectives: This study delves into the evolving image of Filipino nurses in the post-COVID-19 era, a period marked by the transition to long-term management after the lifting of the Public Health Emergency of International Concern (PHEIC) status. Methods: This study employed a quantitative cross-sectional approach, surveying 400 permanent residents of Iloilo City. The Image Scale of the Nursing Profession (ISNP) was employed for data collection, and the analysis was carried out using descriptive and inferential statistics. Ethical clearance was obtained from the Socio-Behavioral Science Research Ethics Review Committee (SBSRERC), ensuring the anonymity and confidentiality of the data. Results: Results indicated a generally positive public perception of nurses across sociodemographic groups, with particularly favorable views in the Professional Qualifications and Status subscales. However, the Education subscale reflects a less favorable public perception. Significant differences were observed across sociodemographic factors, with positive perceptions associated with non-hospital care before the pandemic and hospital care in the past year. Conclusions: While the public in Iloilo City views nurses positively post-pandemic, there are opportunities for improvement, particularly in working conditions and addressing gender biases. Strengthening public awareness of nursing education and research competencies through targeted information campaigns is essential for improving the profession’s image.